Pemberdayaan Masyarakat Melalui Pengolahan Kotoran Ternak Dalam Optimalisasi Kebun Gizi Di Desa Sumberdawesari Kabupaten Pasuruan - Muhammad Ramadhan Muliawan; Nihlatul Falasifah (CV Omah Kreator, 2024)
Sumberdawesari Village, Grati District, Pasuruan Regency, East Java, has become a successful model for livestock farming with increased production and better quality, also providing a positive impact on the local economy, so that breeders have utilized waste processing technology to reduce negative impacts on the environment. Livestock waste in the form of livestock manure is converted into organic fertilizer which is useful for local agriculture, increasing sustainability and resource efficiency in the area. The research method used is a participatory approach that focuses on the community, and the technique for implementing community service activities uses Participatory Rural Appraisal. This technique is usually used in activities related to socio-culture and socio-economics by placing the community as subjects and researchers as insiders who are active in implementing the activities carried out. In making organic fertilizer using a simple compost method. The materials used are livestock manure such as cows, chickens, straw, dry leaves and water. The resulting organic fertilizer was then tested at Gizi Gardens, so that it could produce significant harvest levels. Overall, this activity not only improves soil fertility and plant health, but also strengthens collaboration and practical knowledge in sustainable garden management.